2020
DOI: 10.1186/s13287-020-01839-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of stem cell therapy for burn wounds: a systematic review and meta-analysis of preclinical studies

Abstract: Background Burns remain a serious public health problem with high morbidity and mortality rates worldwide. Although there are various treatment options available, there is no consensus on the best treatment for severe burns as of yet. Stem cell therapy has a bright prospect in many preclinical studies of burn wounds. The systematic review was performed for these preclinical studies to assess the efficacy and possible mechanisms of stem cells in treating burn wounds. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 68 publications
(255 reference statements)
1
22
0
1
Order By: Relevance
“…This result leads to a better effectiveness occurring on a smaller area of the skin flap. Consistent with our finding, a previous meta-analysis concluded that in the application of stem cells to treat burn wounds, smaller burn wounds are more likely to heal effectively [ 62 ]. Overall, the application of stem cells to skin flaps has shown considerable efficacy regardless of the area of the flap.…”
Section: Discussionsupporting
confidence: 92%
“…This result leads to a better effectiveness occurring on a smaller area of the skin flap. Consistent with our finding, a previous meta-analysis concluded that in the application of stem cells to treat burn wounds, smaller burn wounds are more likely to heal effectively [ 62 ]. Overall, the application of stem cells to skin flaps has shown considerable efficacy regardless of the area of the flap.…”
Section: Discussionsupporting
confidence: 92%
“…The primary acquisition of AT-MSC is based on the manually procedure performed with the involvement of lipoaspirate fermentation technique [ 41 ]. The adipose tissue suitable for MSC isolation can be obtained either by skin flaps [ 42 ] or liposuction (LS) [ 43 ].…”
Section: Msc-therapy Of Noamentioning
confidence: 99%
“…Traditional skin wound healing includes four classic phases: haemostasis, inflammation, proliferation and maturation. A meta-analysis showed that stem cell therapy plays a biological role in wound healing, mainly through angiogenesis and anti-inflammatory actions [ 40 ]. HUVECs have offered an important in vitro model for the study of angiogenesis.…”
Section: Resultsmentioning
confidence: 99%